2003
DOI: 10.1292/jvms.65.405
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of Porcine circovirus type 2 DNA in Whole Blood, Serum, Oropharyngeal Swab, Nasal Swab, and Feces from Experimentally Infected Pigs and Field Cases.

Abstract: ABSTRACT. Porcine circovirus type 2 (PCV2) shedding patterns were investigated by polymerase chain reaction (PCR) for the detection of PCV2 DNA, and the diagnostic suitability of a sample for the PCR was examined by using different types of samples. In the e xperimental infection, sixteen pigs were inoculated intranasally with PCV2. The samples, including oropharyngeal and nasal swabs, feces, whole blood and serum became positive for PCV2 DNA by PCR immediately after the inoculation, and almost all samples rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
1
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 14 publications
(23 reference statements)
2
59
1
9
Order By: Relevance
“…This experimental finding is similar to that obtained by a Japanese animal trial that found that PCV2 shedding increases following nursery stages and peaks at 3-4 months of age [22]. The duration of PCV2 shedding in this study among pigs and between herds differed slightly.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…This experimental finding is similar to that obtained by a Japanese animal trial that found that PCV2 shedding increases following nursery stages and peaks at 3-4 months of age [22]. The duration of PCV2 shedding in this study among pigs and between herds differed slightly.…”
supporting
confidence: 90%
“…In a previous in vivo study, 2-week-old pigs challenged with PCV2 had PCV2 DNA in nasal, oropharyngeal and fecal samples on day 1 postinoculation [3]. Another in vivo study demonstrated the PCV2 shedding lasted for at minimum 70 days after viral challenge in weaned pigs [22]. In this study, the onset and duration patterns of PCV2 shedding differed from these findings.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…8,11 Although the pathogenesis and primary mode of transmission of PCV2 are not known, there is evidence to support horizontal and vertical transmission. Porcine circovirus type 2 was detected in ocular, nasal, and fecal secretions from experimentally infected swine 13 and field cases 18 suggesting horizontal transmission. Recently, PCV2 has been cultured from the feces of naturally infected swine suggesting a potential for fecal-oral transmission.…”
mentioning
confidence: 99%
“…O circovírus resiste à inativação quando exposto a ambiente ácido (pH 3), a clorofór-mio, a temperaturas entre 56ºC e 70ºC (Allan et al 1994c), ao congelamento, à luz ultra-violeta e a desinfetantes (Shibata et al 2003). O agente permanece estável em fezes e secreções respiratórias (Shibata et al 2003).…”
Section: Resul II Resul Ii Resul Ii Resul Ii Results T T T Tadunclassified